2018
DOI: 10.11646/zootaxa.4379.4.6
|View full text |Cite
|
Sign up to set email alerts
|

A new species of the Liolaemus alticolor-bibronii group (Iguania: Liolaemidae) from East-central Argentina

Abstract: We describe a new species of Liolaemus of the L. alticolor-bibronii group of the subgenus Liolaemus sensu stricto. We studied meristic, morphometric and qualitative pattern characters. Statistical tests were performed in order to evaluate morphological differences among the candidate species and the most closely geographically distributed species. Molecular analyses of Cyt-b mitochondrial gene were performed in order to estimate the position of the new species in relation to other taxa. We also recorded natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 851 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Many new species of Liolaemus have been described in the last ten years due to the resolution of species complexes (e.g., Breitman et al, 2011b, c;Martinez et al, 2011;Avila et al, 2017), or the discovery of new populations (e.g. Avila et al, 2009Avila et al, , 2012Avila et al, , 2015Troncoso-Palacios et al, 2016;Verrastro et al, 2017;Vega et al, 2018). As the result of a complex evolutionary history,…”
Section: Introductionmentioning
confidence: 99%
“…Many new species of Liolaemus have been described in the last ten years due to the resolution of species complexes (e.g., Breitman et al, 2011b, c;Martinez et al, 2011;Avila et al, 2017), or the discovery of new populations (e.g. Avila et al, 2009Avila et al, , 2012Avila et al, , 2015Troncoso-Palacios et al, 2016;Verrastro et al, 2017;Vega et al, 2018). As the result of a complex evolutionary history,…”
Section: Introductionmentioning
confidence: 99%
“…Abdala et al [22] noted that from 1998 to 2007 an average of five new species of Liolaemus were described annually, but from 2008 to date, 66 new species have been described for an average of 6.5 new Liolaemus per year. The principal evidence used in support of these taxa has been morphological [1, 6, 15, 16, 90, 91, 92, 93, 94], molecular [14, 66, 95, 96, 97, 98, 99], morphological and molecular [5, 19, 100, 101, 102], morphological, molecular, and cytogenetic [18], and phylogenetic [2, 103]. This taxonomic research demonstrates that Liolaemus have morphological characters that are informative for the delimitation of species and that many of these characters are likely to be adaptive, allowing these lizards to exploit a wide range of habitats and macroenvironments, as expressed by the high species richness of the genus [104].…”
Section: Discussionmentioning
confidence: 99%
“…From the first herpetological list to the most recent records (e.g., Ringuelet and Arámburu, 1957; Gallardo, 1977; Tiranti and Avila, 1997; Arzamendia and Giraudo, 2004; Giménez et al, 2008; Cabrera, 2017; Di Pietro et al, 2020a; Vera et al, 2021), a total of 52 species of reptiles have been reported in the Pampas grassland ecoregion (3 turtles, 3 amphisbaenids, 18 lizards, and 28 snakes), among which 7 are narrowly distributed: Contomastix celata Cabrera et al, 2019, Homonota williamsii Avila et al, 2012, Liolaemus absconditus Vega et al, 2018, Li. multimaculatus (Duméril and Bibron, 1837), Li.…”
Section: Methodsmentioning
confidence: 99%